Oral/Perioral Reactions to Injectable Soft Tissue Fillers: A Clinicopathological Multicentric Study - Pires, Fábio Ramoa; Said, Aurélio Marcos Tsutyia; Netto, Juliana de Noronha Santos; da Cruz Perez, Danyel Elias; Bonan, Paulo Rogério Ferreti; Martins, Helder Domiciano Dantas; Kaminagakura, Estela [UNESP]; Alves, Fábio de Abreu; Martelli Júnior, Hercílio; Machado, Renato Assis; Lopes, Márcio Ajudarte; Santos-Silva, Alan Roger; et al. (Wiley, 2024)
Objective: To analyze the characteristics of a series of oral reactions to injectable soft tissue fillers. Materials and Methods: Cases diagnosed as oral reactions to injectable soft tissue fillers were selected from eight Pathology laboratories. Information was retrieved from the laboratory charts and from the review of the hematoxylin and eosin-stained histological slides. Results: The 151 patients showed a mean age of 54.9 years, and 136 (90.1%) were females. Mean time of onset was 20.4 months, and the lips were the most frequent location (72.8%). Most cases presented as asymptomatic isolated nodules, with a mean size of 17.4 mm. Silicone (38.5%), polymethylmetacrylate (33%), and hyaluronic acid (11.9%) were the three most common fillers. Granulomas, foamy macrophages, and multinucleated giant cells were observed in 44%, 51.5%, and 65.3% of the cases, respectively. Time of onset was shorter for males (p = 0.033), and symptoms were common in the upper lip, buccal mucosa, and lower vestibule (p = 0.010). Foamy macrophages were more common in association with silicone and collagen (p < 0.001), whereas multinucleated giant cells were more common in association with polymethylmetacrylate, hydroxiapatite, and polylactic acid (p = 0.012). Conclusion: Clinicians should consider reactions to injectable soft tissue fillers when evaluating asymptomatic submucosal nodules affecting the lips of adult/older females.
Keywords: filling; hyaluronic acid; lips; polymethylmetacrylate; reactions; silicone